Advances in Crosstalk between Porcine Circoviruses and Host - Guyu Niu; Si Chen; Xue Li; Liying Zhang; Linzhu Ren (Viruses, 2022)
Porcine circoviruses (PCVs), including PCV1 to PCV4, are non-enveloped DNA viruses with a diameter of about 20 nm, belonging to the genus Circovirus in the family Circoviridae. PCV2 is an important causative agent of porcine circovirus disease or porcine circovirus-associated disease (PCVD/PCVAD), which is highly prevalent in pigs and seriously affects the swine industry globally. Furthermore, PCV2 mainly causes subclinical symptoms and immunosuppression, and PCV3 and PCV4 were detected in healthy pigs, sick pigs, and other animals. Although the pathogenicity of PCV3 and PCV4 in the field is still controversial, the infection rates of PCV3 and PCV4 in pigs are increasing. Moreover, PCV3 and PCV4 rescued from infected clones were pathogenic in vivo. It is worth noting that the interaction between virus and host is crucial to the infection and pathogenicity of the virus. This review discusses the latest research progress on the molecular mechanism of PCVs–host interaction, which may provide a scientific basis for disease prevention and control.